Selection of Potential Isolates of Azospirillum for Growth Enhancement in Teak - Radhakrishnan, Ayswarya; Mohan, V. (Indian Forester, 2010)
Thirty two isolates of Azospirillum were isolated from the teak growing areas of Andhra Pradesh, Kerala and Tamil Nadu in South India. The isolates were identified, mass cultured and mixed with carrier material and inoculated to tissue culture raised plantlets of teak in nursery condition to test the efficacy of the isolates on the growth, biomass production and the overall quality of the plantlets. It was found that the isolates ACH-4 (Andhra Pradesh) and KNI-2 (Kerala) were the most potential ones for the growth improvement of the teak plantlets. An attempt was made to determine the synergistic effect between these 2 isolates and it was observed that application of both the isolates put together, not only enhanced the growth but also increased the biomass and the quality of the plantlets.